Dochody rolnicze ludności chłopskiej jako czynnik postępu cywilizacyjnego na wsi w Polsce Ludowej - Czyżewski, Andrzej (Wydział Prawa i Administracji UAM, 1982)
The assumption was made by the author that changes of the income situation of farm population are reflected in the developement or setbacks of the civilizational progress of the country. It was identified with changes in the living standards of farmer families. In consequence much attention was devoted to the proportions of distribution of earned income in agriculture, in order to emphasize the relation between economic base of individual holdings and changes in material living conditions of farm population. The article is opened with the analysis of tendencies of agricultural income shaping which at the same time serves as the source of information on the economic revival and recession in the country i.e. on their periodical division. Further deliberations indicate at the interrelations between economic base of farms and the level of consumption and the interest in non-productional investments. Particular importance is attributed to the expenditures belonging to the sphere of the so-called "other consumption" which is treated as an indicator of the civilizational progress of the country. There are also comparisons drawn on the rate of growth of work efficiency of the employed in farming and on consumer's money. That can visualize a role of the price factor in the processes of progress in the country. The conclusions indicate that fluctuations in the level and rate of growth of agricultural income can influence the reproductive processes in farms. In case of negative fluctuations they were manifested not by limiting productional investments but by changes in invetntories and in herds (stocks) which is mostly in the field of breeding. At the same time farms developed their productional investments as much as they could, without relating it to current profitability of production. They realized that the increase in profitability has to come, however as the experience taught, it would be short-lived, on account of the fact that purchase prices are not adjusted to the level of living costs. That type of reasoning, espesially the strife of farms to strengthen their economic foundations by means of investment can on the one hand prove the vitality and rationality of that economy, and the other- the openness to the processes of progress in the country. These latter, however, were halted by agricultural policies of the Statte, pariticuilarly as regards prices. It is also found that the developement of consumption and of non-productional investmeats in the country was of a cyclical character. It influenced directly shaping of the civilizational progress in the country. The driving force of that process i.e. the economic base of private farms was narrow and changing over time. Some tendencies of its increase have been marked throughout the examined period. That process was however slow and not without disturbances.
Agricultural Income of the Farm Population as a Means of the Civilizational Progress of the Country in the People's Poland